Thermomechanical characterization of an amylose-free starch extracted from cassava (Manihot esculenta, Crantz) - Pulido Diaz, Adriana; Lourdin, Denis; Della Valle, Guy; Fernández Quintero, Alejandro; Ceballos, H.; Tran, Thierry; Dufour, D.L. (Elsevier, 2017)
The aim of this study was to determine and compare the melting (Tm), glass transition (Tg) and mechanical relaxation (Tα) temperatures of a new waxy cassava starch. Thermal transitions measurements were obtained by Differential Scanning Calorimetry (DSC) and Dynamical Mechanical Thermal Analysis (DMTA). The experimental data showed a high correlation between water volume fraction and melting temperature (Tm) indicating that the Flory-Huggins theory can be used to describe the thermal behavior of this starch. The Tm of waxy cassava starch-water mixes were lower than a waxy corn starch-water reference system, but differences were not statistically significant. The mechanical relaxation temperatures taken at tan δ peaks were found 29–38 °C larger than Tg. The Tα and Tg measured for waxy cassava starch exhibited similar properties to the ones of waxy corn starch, implying that waxy cassava starch can be used in food and materials industry.